Understanding knowledge threatened by declining wild orchid populations in an urbanizing China (Sichuan). (24th July 2019) - Seyler, Barnabas C; Gaoue, Orou G; Tang, Ya; Duffy, David C
Summary: With rapid urbanization worldwide, most people now live in cities, but the effects of urbanization on knowledge about the natural environment is not well studied. Due to the importance of Cymbidium to Chinese traditional culture, we tested how urbanization influences the distribution of orchid knowledge across various knowledge domains at risk of loss due to declining orchid populations. Participants in the Cymbidium trade were interviewed in three distinct urbanization-level jurisdictions in Sichuan, China: Puge (low urbanization), Huili (moderate urbanization) and Chengdu (high urbanization). Using photographic cue-cards of nine Cymbidium taxa, we assessed aggregate and specific knowledge held by 91 orchid collectors/traders across the urbanization gradient. Contrary to expectations, we found that urbanization and orchid knowledge were positively related, but this varied by knowledge type, with moderate urbanization showing significantly higher knowledge in two domains. Our findings suggest that a generalizable understanding of how urbanization affects knowledge must account for differences in knowledge types and geographic/cultural scales, with implications for biocultural diversity conservation in an increasingly urban world.